2004
DOI: 10.1128/mcb.24.13.5835-5843.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Amplification of Mdmx (or Mdm4) Directly Contributes to Tumor Formation by Inhibiting p53 Tumor Suppressor Activity

Abstract: Human tumors are believed to harbor a disabled p53 tumor suppressor pathway, either through direct mutation of the p53 gene or through aberrant expression of proteins acting in the p53 pathway, such as p14 ARF or Mdm2. A role for Mdmx (or Mdm4) as a key negative regulator of p53 function in vivo has been established. However, a direct contribution of Mdmx to tumor formation remains to be demonstrated. Here we show that retrovirus-mediated Mdmx overexpression allows primary mouse embryonic fibroblast immortaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
300
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(313 citation statements)
references
References 43 publications
11
300
2
Order By: Relevance
“…98 Somatic MDM2 amplification has been considered an alternative mechanism of p53 inactivation, and is commonly recorded in soft tissue and osteosarcomas and gliomas, less frequently in melanomas and colon cancer. [99][100][101][102] Amplifications of MDM4 has been reported albeit at low incidence in breast cancers and gliomas, 102,103 and in retinoblastomas (RBs), for which experimental evidence indicates a role in tumour progression. 104 Interestingly, MDM4 overexpression has been associated with lack of response to the MDM2 antagonist nutlin in chronic lymphoma cells in vitro.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%
“…98 Somatic MDM2 amplification has been considered an alternative mechanism of p53 inactivation, and is commonly recorded in soft tissue and osteosarcomas and gliomas, less frequently in melanomas and colon cancer. [99][100][101][102] Amplifications of MDM4 has been reported albeit at low incidence in breast cancers and gliomas, 102,103 and in retinoblastomas (RBs), for which experimental evidence indicates a role in tumour progression. 104 Interestingly, MDM4 overexpression has been associated with lack of response to the MDM2 antagonist nutlin in chronic lymphoma cells in vitro.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%
“…In addition, it has been reported that Mdm4 can enhance Mdm2-mediated ubiquitination and degradation of p53 (Stad et al, 2000. Similar to Mdm2, Mdm4 has been found overexpressed in a significant number of various human tumors and tumor cell lines, in general correlating with the expression of wild-type p53, suggesting that Mdm4 contributes to p53 inactivation during tumorigenesis (Riemenschneider et al, 1999(Riemenschneider et al, , 2003Ramos et al, 2001;Danovi et al, 2004;Laurie et al, 2006). As both Mdm2 and Mdm4 are overexpressed in many tumors that retain wild-type p53, they are attractive targets for the development of anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of Mdm2 causes cell cycle arrest and in some cases apoptosis in tumourderived cells expressing wild-type p53 (Vassilev, 2007). Inhibiting MdmX can also have anti-tumour activity (Danovi et al, 2004;Gilkes et al, 2006). However, targeting both Mdm2 and MdmX in cancer cells has been observed to have a greater pro-apoptotic effect than targeting either alone (Hu et al, 2006;Patton et al, 2006;Wade et al, 2006;Xia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%